Institutionalized corruption in Indonesian irrigation: an analysis of the upeti system - Suhardiman, Diana; Mollinga, P.P. (2017)
This article analyzes the internal logic of the upeti system in Indonesian irrigation and brings to light how corruption rules are shaped through complex socio-political relationships reflected in the organizational culture of the irrigation agency. Based on 100 interviews with water sector professionals the article highlights: (1) the importance of social relations in shaping institutionalized corruption, (2) how the upeti system justifies corruption practices as the prevailing social norm, and (3) the need for structural change to eradicate corruption. Illustrating how corruption rules are embedded in project management procedures, with projects highly dependent on donor funding, the article highlights the importance of the issue for international agencies and the need to be more politically grounded in promoting their development agenda.